SKRIPSI IMPLEMENTASI KECERDASAN BUATAN PADA GAME MENGGUNAKAN METODE PATHFINDING DENGAN GAME ENGINE UNITY3D - Edi Heriyanto; Erna Kumalasari Nurnawati; Dina Andayati (Jurnal SCRIPT, 2018)
Artificial intelligence is one part of computer science that makes machines (computers) can do work like humans and computers is possible to be able to think. However, for now in accordance with the development of games and artificial intelligence applied. In artificial intelligence based games, there are many techniques adapted from the field of artificial intelligence to be applied to the game. Some of them are: Chasing and Evading, Movement Patterns and Pathfinding, Neural Networks and Genetic Algorithms (Genetic Algorithm). Pathfinding method is most easily encountered in game-type games where we designate a character (player) to be moved to a particular location by clicking on the location to be addressed. The player will move in the right direction, and "smart" can find the shortest path or avoid the obstacles. Artificial intelligence is needed in the making of the game, which is to design and produce fun games and inter-safe machine that is smart and interesting to play. The results of this study is a game that there are three types of artificial intelligence that is stupid enemies, brutal enemies and intelligent enemies programmed using pathfinding method with game maker software that is Unity3D.